The protective effect of Boswellic acid and Ellagic acid loaded, colon targeted, and pH-sensitive N-succinyl chitosan in ulcerative colitis rat model - Yipel, Mustafa; Tekeli, Ibrahim Ozan; Altinok-Yipel, Fulya; Coskun, Pinar; Aslan, Abdullah; Guvenc, Mehmet; Ozsoy, Sule Yurdagul (Elsevier, 2022)
Targeted drug delivery systems that provide therapeutic activity with lower concentrations of both herbal and other substances, while reducing access to non-target sites and undesirable effects; have an important potential for future projections in terms of pharmacological and toxicological studies. The present study aimed to investigate the protective effects of Acetyl 11-keto-beta-boswellic acid (AKBA) and Ellagic acid (EA) loaded, colon targeted, and pH-Sensitive N-succinyl chitosans (NsCh) in ulcerative colitis (UC) model induced by acetic acid (AA) in rats. The physicochemical characterization (elemental analysis, FT-IR, DSC, XRD, SEM, NMR) analyses, swelling, and releasing tests of NsCh's suggested that AKBA and EA were successfully loaded to pH-sensitive polymer and targeted to the colon. The targeted AKBA and EA were administered to Wistar rats (n:30, 5 groups) and damage, inflammatory cytokine, protein expression, oxidative stress, and antioxidant parameter levels in colon tissues of the groups were determined. Increase in the levels of CAT, GPx activities, and decrease in necrosis, inflammation, and levels of MDA, TNF-alpha, COX-2, NF-kB were observed in the targeted EA and AKBA groups compared to the UC group. The potential protective effect of EA and AKBA loaded, colon-targeted, pH sensitive controlled releasing system against UC and the potential to be licensed preparations by completing the next stages of in vitro and in vivo studies were demonstrated.
Keywords: Colon targeting; 11-Keto-? -boswellic acid; Ellagic acid; N-Succinyl chitosan; Ulcerative colitis